Influence of Pupils Interpretation of Kenyan Sign Language on Academic Performance of Pupils with Hearing Impairment in Selected Public Prim ary Schools, Kenya - M Wawire, Tom; Namunga, Nick (2019)
The government of Kenya recognizes the importance of special needs edu cation as a crucial sector for accelerating the attainment of Educatio n for all students and the 2030 Millennium Development Goals. The purp ose of this study was to establish the relationship between mastery of Kenya Sign Language (KSL) and academic performance of pupils with hea ring impairment in public primary schools in western Kenya. Study obje ctive was to find out the influence of pupils’ interpretation of Kenya Sign Language on academic performance. The study employed a mixed res earch approach and a descriptive survey design to collect qualitative and quantitative data. Using purposive sampling technique, 12 head tea chers, 93 teachers and 108 pupils with hearing impairment forming a sa mple size of 213 respondents. Research instruments used were a Likert scale questionnaire and interview schedule. Piloting of the questionna ire was done in a public special primary school for the pupils with he aring impairment in Birunda School for the Deaf in Trans Nzoia. The co llected data was analysed using descriptive statistics of frequencies, percentages, means, standard deviation and Pearson correlation coeffi cient and inferential statistics of chi-square using the statistical p ackage for social sciences [SPSS] program of version 23. Qualitative d ata was analysed by describing the emerging themes in relation to the study objectives. The study established that there was significant rel ationship between pupils’ interpretation of KSL at p<0.05. Therefore, the null hypothesis was rejected and concluded that mastery of KSL sig nificantly influences academic performance. The results will help stak eholders in the education sector to establish how KSL is used in the t eaching of pupils with hearing impairment in schools, hence providing valuable data on the current policy and practice in the field of educa tion and training of teachers of the learners with hearing impairment. The following recommendations were made: pupils should be equipped wi th more interpretation and literacy skills for the KSL, further traini ng in special needs education be given to teachers and adequate resour ces and support services be given to the learners.